PERAN MEDIA PEMBELAJARAN DALAM PENINGKATAN PEMAHAMAN SISWA SEKOLAH DASAR PADA MATAPELAJARAN MATEMATIKA - NIT, Nita Syahputri; Indriani, Ulfah (Journal Information System Development (ISD), 2018)
Mathematics is one of the subjects that tend to be less favored by students, especially the students of grade 1 primary school. The students prefer to draw or other mathematics that are visual compared to mathematics. Therefore, in this research try to combine the mathematical material in the form of visual which is animation and also use the character of drawing which is liked by the children, so that the student is more interested in the learning process of mathematics. Selection of programming in writing this research using macromedia flash application. With the help of information technology and programming languages, especially animation, there will be many benefits that can be obtained. In this case the teacher is easier in delivering the material and students more easily in absorbing the material delivered so that the learning process can run more effectively and efficiently. And with the role of this learning media can overcome the problem of lack of interest in learning students of mathematics subject matter and of course increase the value of students in exercises or exams conducted in schools.Â Keywords: Role; Media; Learning; Math